Usefulness of dermoscopy in congenital melanocytic nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
In the adult the dermoscope is mainly used to increase sensitivity and specificity in the diagnosis of melanoma. The latter indication is less important in the prepuberal age, given the extreme rarity of melanoma at this age. However, also at this age the dermoscope can be useful, as shown by the case here reported. The dermoscope can be useful to differentiate more easily melanocytic from vascular structures -for instance angiokeratoma from nevus, pigmentary purpura from lichen in its pigmentary phase, intranevic hemorrhage-, to suspect, even when precise history data lack, a rapidly growing nevus of the Reed type. The dermoscope is also useful to diagnose and study numerous parasitoses, from scabies to pediculosis, demodicidosis and tungiasis (1, 2).